![image](https://tex.z-dn.net/?f=y%3D-xe+%5E%7B1-2x%5E2%7D+%5C%5C%0Ay%27%3D-e%5E%7B1-2x%5E2%7D%2B%28-x%5Ccdot+e%5E%7B1-2x%5E2%7D%5Ccdot%28-4x%29%29%5C%5C%0Ay%27%3D-e%5E%7B1-2x%5E2%7D%2B4x%5E2e%5E%7B1-2x%5E2%7D%5C%5C%0Ay%27%3De%5E%7B1-2x%5E2%7D%284x%5E2%7D-1%29%5C%5C%0Ae%5E%7B1-2x%5E2%7D%284x%5E2%7D-1%29%3D0%5C%5C%0A4x%5E2-1%3D0%5C%5C%0A4x%5E2%3D1%5C%5C%0Ax%5E2%3D%5Cfrac%7B1%7D%7B4%7D%5C%5C%0Ax%3D-%5Cfrac%7B1%7D%7B2%7D+%5Cvee+x%3D%5Cfrac%7B1%7D%7B2%7D%5C%5C%0A%5Cforall_%7Bx%5Cin%28-%5Cinfty%2C-%5Cfrac%7B1%7D%7B2%7D%29%7D%5C+y%27%3E0%5CRightarrow+y+%5Cnearrow%5C%5C%0A%5Cforall_%7Bx%5Cin%28-%5Cfrac%7B1%7D%7B2%7D%2C%5Cfrac%7B1%7D%7B2%7D%29%7D%5C+y%27%3C0%5CRightarrow+y+%5Csearrow%5C%5C%0A%0A%0A%0A%0A%0A)
0\Rightarrow y \nearrow\\
\forall_{x\in(-\frac{1}{2},\frac{1}{2})}\ y'<0\Rightarrow y \searrow\\
" alt="y=-xe ^{1-2x^2} \\
y'=-e^{1-2x^2}+(-x\cdot e^{1-2x^2}\cdot(-4x))\\
y'=-e^{1-2x^2}+4x^2e^{1-2x^2}\\
y'=e^{1-2x^2}(4x^2}-1)\\
e^{1-2x^2}(4x^2}-1)=0\\
4x^2-1=0\\
4x^2=1\\
x^2=\frac{1}{4}\\
x=-\frac{1}{2} \vee x=\frac{1}{2}\\
\forall_{x\in(-\infty,-\frac{1}{2})}\ y'>0\Rightarrow y \nearrow\\
\forall_{x\in(-\frac{1}{2},\frac{1}{2})}\ y'<0\Rightarrow y \searrow\\
" align="absmiddle" class="latex-formula">